PHASE STUDY OF TITANIUM DIOXIDE NANOTUBES FABRICATED VIA ANODIZATION IN HF ELECTROLYTE - A'liya Abdul LAZIZ; Alaba O. ARAOYINBO (European Journal of Materials Science and Engineering, 2017)
This study focused on the phase study of titanium dioxide (TiO2) nanotube fabricated via anodization in HF solution. The objectives of this study is to observe the structure of nanotube formed after anodizing the titanium foil at different pH using field emission-scanning electron microscope and to analyze the different phases of TiO2 heat treated at different temperature using X-ray diffraction tool. In order to form the TiO2 nanotube, various parameters were used during the anodization process. The parameters include pH value of the HF solution, anodizing time, and applied potential. The pH of HF solution used is 1, 5 and 9 for 10 minutes time duration at 20 V. The TiO2 nanotubes were heat treated at temperatures of 300, 500 and 700C with soaking time of 3 hours and cooling rate of 5C/min in a tube furnace to produce different phase of titanium dioxide. Phase identification from the titanium dioxide characterization indicates the presence of rutile and anatase peaks. The optimal condition for TiO2 nanotubes formation was pH 5 with an applied potential of 20 V.